Impact of cryopreservation on DNA damage in Acer platanoides L. seeds evaluated by the comet assay - Beata P. Plitta-Michalak; Alice A. Ramos; Magdalena Trusiak; Ewelina Ratajczak; Marcin Michalak (Scientific Reports)
Abstract Plant cells can suffer significant damage during cryopreservation, primarily due to extensive ice punctures and oxidative stress from reactive oxygen species (ROS). The extent of damage is closely linked to the moisture content (MC) of seeds, a crucial factor influencing their viability after cryostorage. However, there is limited information on the direct effects of MC in cryostored seeds on their overall (epi)genetic integrity. Maintaining genome integrity is essential for plant growth and ensures reliable transmission of genetic information. To investigate seed responses to genotoxic stress from desiccation and cryostorage, specific DNA damage, including DNA strand breaks, alkali-labile sites, and 8-oxo-7,8-dihydroguanine (8-oxoG), was measured, along with changes in epigenetic marks 5hmC (5-hydroxymethylcytosine) and 5mC (5-methylcytosine). This is the first study to demonstrate fine DNA strand breaks in orthodox seeds of Acer platanoides L. at varying MC immediately after cryostorage. Notably, 8-oxoG was detected for the first time in plant samples after cryostorage, and it was negatively correlated with seed viability, whereas the epigenetic marks showed a positive correlation. These findings indicate that cryostorage at non-optimal MC levels is genotoxic for seeds. Furthermore, the study demonstrated that the comet assay is a valuable technique for monitoring global DNA integrity in cryopreserved plant material.